Update of the epiphytic flora of Peru - Mondragón, Demetria (2024)
Despite the high diversity of vascular epiphytes (VE) reported in Peru, there is no updated checklist that is in line with the new taxonomic delimitations and the new concepts of epiphytes. In this study, we update the list of VE in Peru, based on a bibliographic search and visits to local herbaria. Species names were updated according to the World Flora Online, their presence in the EpiList was confirmed, as well as their altitudinal distribution and distribution by department, risk category, and endemism. Finally, the epiphyte coefficient was estimated. We found 2462 species, belonging to 18 orders, 25 families, and 249 genera. The families with the highest richness were Orchidaceae (1606), Bromeliaceae (201), and Piperaceae (139 spp.); 85% of the species were in the EpiList (2088 spp.). The department with the highest richness was Amazonas (709) and the lowest were Ica and Tacna (2 spp.). The altitudinal range with the highest richness is between 1501 – 2000 m (649); 689 species are endemic and 220 are in some risk category; the epiphyte quotient is 13.12. This update represents an approximate 40% increase, positioning Peru as the third country with the highest VE diversity. A more comprehensive list was obtained, in line with the concept of epiphytism, highlighting the need to include 384 species in the EpiList, which would help complement the global list of VE worldwide.